2020
DOI: 10.1016/j.yebeh.2020.107363
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between neuromagnetic activity and cognitive function in benign childhood epilepsy with centrotemporal spikes

Abstract: Our aim was to explore the pathophysiological mechanism of cognitive function changes in early untreated children with benign childhood epilepsy with centrotemporal spikes (BECTS). Methods: Magnetoencephalography (MEG) was performed in 33 children with BECTS and 18 healthy children. Wechsler Intelligence Scale for Children, fourth edition (WISC-IV) was used to divide children with BECTS into two groups. Normal cognitive function was defined as a full-scale intelligence quotient (FSIQ) of N 80, while decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 43 publications
(66 reference statements)
0
8
0
Order By: Relevance
“…In addition, we did not find a significant correlation between the age at onset and duration of illness. We do not believe that there is a simple linear relationship between magnetic source intensity, age at onset, number of episodes, and duration of illness, which we plan to reconfirm in a larger sample ( 45 ).…”
Section: Discussionmentioning
confidence: 93%
“…In addition, we did not find a significant correlation between the age at onset and duration of illness. We do not believe that there is a simple linear relationship between magnetic source intensity, age at onset, number of episodes, and duration of illness, which we plan to reconfirm in a larger sample ( 45 ).…”
Section: Discussionmentioning
confidence: 93%
“…The verbal comprehension index (VCI) represents language and verbal skills, the perceptual reasoning index (PRI) reflects nonverbal and fluid reasoning, the working memory index (WMI) reflects working memory and auditory attention, and the processing speed index (PSI) reflects selective attention and speed of visual information processing. We previously reported that, prior to treatment, children with CECTS showed significantly poorer performance compared to health controls in all aspects (Li et al, 2020a). The WISC-IV was utilized in the present study to determine whether treatment with AEDs would cause a change in cognitive function.…”
Section: Neurocognitive Assessmentmentioning
confidence: 99%
“…Since each node-beam lead field indicated a form of either source-beamformer or subspace solution, the ASI had multiple source beamformers to separate correlated sources. Several previous studies have verified the reliability of this method (Xiang et al, 2014(Xiang et al, , 2015aLiu et al, 2015;Tang et al, 2016;Li et al, 2020c;.…”
Section: Discussionmentioning
confidence: 61%